Analisis Pengendalian Kualitas Produk Ayam Utuh pada PT XYZ dengan Metode Statistical Quality Control (SQC) - Miskiyah, Aliffatul; Pulansari, Farida (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2025)
PT. XYZ is a producer of slaughtered chicken and has a chicken slaughterhouse with the largest production capacity in Indonesia. PT XYZ has various types of products, the most in demand is whole chicken, but in the production process, whole chicken products have a greater number of defects than other products. The solution of the problem can be done using the Statistical Quality Control (SQC) method. This study aims to identify and analyze the quality of whole chicken products in PT XYZ using the Statistical Quality Control (SQC) method, determine the factors that cause non-conformities in whole chicken products, and find out improvement efforts using 7 stages of more detailed and detailed problem solving, such as Check Sheets, Pareto diagrams, scatter charts, histograms, control charts, stratifications, and fishbone diagrams. Based on the data processing, the following results were obtained, out of a total sample of 170,800 whole chickens, there were 16,149 that experienced non-conformities; Based on Pareto chart analysis, the dominant types of defects were abnormal Leg Cutters (59%), blistered chicken wings (22%), and broken chicken wings (19); Process stability: Analysis of the control chart shows that the production process is out of control at some point, indicating that there are variations that need to be corrected. This research can increase knowledge about analytical models and product quality.